Hubungan Lamanya Penggunaan Alat Kontrasepsi Hormonal Suntik Tiga Bulan dengan Hipertensi - Fatmawati, Ariani; Mulyani, Mulyani; Lusiani, Eli (Jurnal Kesehatan Holistic, 2020)
Hormonal contraception is the most popular, most participants use contraceptive hormonal contraception for three months injection. This study aims to determine the relationship between the length of use of three months of injectable contraceptive hormonal contraception with the incidence of hypertension in the working area of ??UPT Puskesmas Kopo, Bandung. This type of research is quantitative research with cross-sectional approach. The population in this study were all mothers who used three-month injection KB in the working area of ??the Kopo Puskesmas UPT as many as 741 people. The sampling technique used was accidental sampling with a total sample of 101 respondents. Data collection was carried out directly using demographic data sheets and blood pressure measurements were carried out in accordance with research procedures. When the study was conducted in November - December 2019. The analysis used was the Chi-Square statistical test. The results showed that there was a relationship between the length of use of three months of injectable contraceptive hormonal contraception with the incidence of hypertension (p = 0,000). Research suggestions, provide counseling to injecting family planning acceptors three months more than 5 years to switch to non-hormonal contraceptives. This is intended to stabilize hormone levels in the body.